1973
DOI: 10.1037/h0035627
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of patient and attendant reinforcement programs: The "piggyback" effect.

Abstract: The purpose of this study was to develop an experimental approach for assessing the possible interaction of separate reinforcement programs for attendants and patients on an open psychiatric ward. Patients were reinforced with lunch for engaging in work behavior. Attendants were reinforced with trading stamps for successfully completing assigned behavior modification tasks. Interactions were defined as the effects on the patients' work behavior of introducing and removing the reinforcements for attendants. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

1976
1976
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Earlier research, particularly that of the 1970s, heavily emphasized accompanying social consequences with monetary-type backups for feedback (e.g., Bricker, Morgan, & Grabowski, 1972;Hollander & Plutchik, 1972;Hollander, Plutchik, & Horner, 1973;Katz, Johnson, & Gelfand, 1972;Pommer & Streedbeck, 1974). At that time, research was not so much concerned with client outcomes, but more about demonstrating changes in staff performance.…”
Section: Supervisory Feedbackmentioning
confidence: 95%
“…Earlier research, particularly that of the 1970s, heavily emphasized accompanying social consequences with monetary-type backups for feedback (e.g., Bricker, Morgan, & Grabowski, 1972;Hollander & Plutchik, 1972;Hollander, Plutchik, & Horner, 1973;Katz, Johnson, & Gelfand, 1972;Pommer & Streedbeck, 1974). At that time, research was not so much concerned with client outcomes, but more about demonstrating changes in staff performance.…”
Section: Supervisory Feedbackmentioning
confidence: 95%
“…Appreciation is expressed to Robert E. Crow, Terry Page, Kenneth E. Bauman, and John D. Cone for their assistance in writing the manuscript, to Barb Lowther for assistance in data collection, to Cheryl Trgovich for assistance in preparing the manuscript, and to Mary Ann Powers for her project suggestions. Reprints may be obtained from Dennis H. Reid (Bricker, Morgan, and Grabowski, 1972;Hollander and Plutchik, 1972;Hollander, Plutchik, and Horner, 1973) as reinforcing stimuli. Group contingencies (Reid, Schuh-Wear, and Brannon, 1978) and behavioral lotteries (Iwata, Bailey, Brown, Foshee, and Alpern, 1976) have also received attention.…”
mentioning
confidence: 99%
“…Using measurement procedures such as paper and pencil tests and ability inventories performed in controlled situations, it has been demonstrated that inservice programs can increase both verbal knowledge (Cochran and Steiner, 1966;Gardner, 1972a;Johnson and Ferryman, 1969) and training skills (Gardner, 1972b;Panyan and Patterson, 1974). On the other hand, studies in which staff or resident behavior was repeatedly monitored under natural conditions have suggested that instructions, training, and the development of job assignments may be expected to have relatively small (Martin, 1972), temporary (Hollander, Plutchik, and Horner, 1973;Panyan, Boozer, and Morris, 1970), or negligible effects (Hollander and Plutchik, 1972;Katz, Johnson, and Gelfand, 1972;Quilitch, 1975) on attendants' actual work performance.…”
mentioning
confidence: 99%
“…Frequent monetary bonuses, either alone (Katz et al, 1972), or in combination with other procedures such as assignments (Martin, 1972;Pommer and Streedbeck, 1974) and rankings (Pomerleau, Bobrove, and Smith, 1973), are extremely effective techniques. Additional reinforcers have included commercial trading stamps (Bricker, Morgan, and Grabowski, 1972;Hollander and Plutchik, 1972;Hollander et al, 1973) and extra time off from work (Watson, 1972b).…”
mentioning
confidence: 99%